An Analysis of the Relationship Between Government Spending and Economic Growth in Developing Countries: A Qualitative Analysis of Spending Size, Composition, and Fiscal Efficiency - Maulina Nabila; Dayuni Dayuni; Ahmad Bahar Sagita; Gina Puspita; Muhammad Saied (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2026)
The debate over the relationship between government spending and economic growth in developing countries is never over because the empirical findings are far from uniform. This article examines this relationship through a critical literature review enriched by descriptive analysis of secondary data from the World Development Indicators, the IMF's Fiscal Monitor, and World Bank reports and working papers. The focus of the analysis is placed on three dimensions: the size of spending, the composition of spending, and the efficiency of fiscal management. The results of the synthesis show that government spending does not work automatically as a growth engine. The size of the budget is important, but its influence is largely determined by the structure of spending, the quality of institutions, fiscal space, and the ability of the state to convert spending into physical capital and productive human capital. Public investment spending tends to have a more pronounced growth impact when efficiency is high, fiscal space is adequate, and projects are selectively selected. On the other hand, education and health spending more often shows a gradual impact, with long-term benefits that depend on the quality of services, rather than simply a nominal increase in spending. The main implication is that the fiscal agenda in developing countries should shift from simply enlarging the budget to improving the composition, governance, and effectiveness of public spending.